Career Choice Shift of the English Students Based on Gender - Arifuddin Arifuddin; Kamaludin Yusra; Ahmad Zamzam; Arafiq Arafiq; Lalu Jaswadi Putra; Dewa Gede Ngurah Byomantara (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of Study: Exploring the students’ motivations for studying in the English departments, comparing career choices and interests based on gender, and determining the ‘time’ and reasons for shifting careers. Methodology: This study employed mixed methods. The sample was drawn through proportional random sampling and involved 1100 students from the English departments in Lombok, Indonesia. 380 male and 820 female students, more than 25 percent of the total, filled out the Google Forms questionnaire. The data were collected through questionnaires and academic documents. Quantitative data analysis employed descriptive statistics, while qualitative analysis used ‘Iterative Analysis.’ Main Findings: 1) Being a teacher is the primary motivation for studying in the English departments; 2) Females far dominate men in the choice of the teaching profession, while males in the tourism and hospitality sector; 3) But, career choice shift occurs at the end of the study motivated by socio-economic orientation. So, curriculum developers should consider biological and socio-cultural aspects of English education gender. Further studies should be conducted on the interrelation of gender and socio-cultural and religious perspectives. Novelty/Originality of this Study: The choice of work of the students of the English departments in Indonesia is still determined by its suitability with gender. Some studies on career shifts in universities have been carried out, but a specific study that explored the career choice shift of English department students based on gender has never been carried out. This is the ‘novelty.’ Nevertheless, this study did not include the students’ religion-based educational background.